ASSOCIATION OF AGE OF MENARCHE WITH BODY MASS INDEX AND WAIST-HIP RATIO IN SCHOOL GOING GIRLS (Journal of Pharmaceutical Negative Results, 2023)
Background and Objectives: Age of Menarche is affected by various genetic (sex, race, parental inﬂuence), environmental (body fatness, nutrition) and socioeconomic/cultural factors (e.g., immigration status). In this study, we have analysed association of age of menarche with BMI, WHR, parent’s education and occupation.Materials and Methods: The study included 72 girls who had attained menarche during the study or within six months prior to the study. Their primary details (name, age) time of menarche, parent education and occupation were collected using questionnaires, height (in cm) and weight (in kg) were measured. BMI and WHR was calculated and analysis was done by Epi Info 7 software.Results: When comparing private and government school for mean age of menarche it was found that the mean menarche age in high WHR was lower in private school. So, there must be some other confounding factors responsible for lower age of menarche in private school. In the government school, the mean age of menarche was almost similar in BMI categories. However, in private school underweight girls were found to have lower mean age of menarche. Overall, Mean age of menarche of private school was lesser than government school girls. No correlation was found between mean age of menarche and parents education and occupation.Conclusion: There was positive correlation between anthropometric measurements and age of menarche. Howerver, all are weak correlations.